Collagen scaffolds tethered with bFGF promote corpus spongiosum regeneration in a beagle model. (20th February 2018) - Tang, He; Jia, Weisheng; Hou, Xianglin; Zhao, Yannan; Huan, Yong; Chen, Wei; Yu, Wei; Ou Zhu, Mi Ma; Ye, Gang; Chen, Bing; Dai, Jianwu
Abstract: Regeneration of the corpus spongiosum helps prevent complications following urethral reconstruction, but currently there is a lack of effective therapeutic methods in clinic. In previous studies, we fabricated a fusion protein collagen-binding domain (CBD)-basic fibroblast growth factor (bFGF) that specifically binds to and releases from collagen biomaterials. We demonstrated that CBD-bFGF could promote angiogenesis and tissue regeneration in vivo . In this study, we established a beagle model with extensive urethral defects, and reconstructed the defects with collagen biomaterials that were unmodified or modified with CBD-bFGF. The results demonstrate that CBD-bFGF promotes corpus spongiosum regeneration resulting in improved outcomes following urethral reconstruction. Modifying collagen biomaterials with CBD-bFGF may represent an effective strategy for urethral substitution in urethral reconstruction.